Dealing with Private Debt Distress in the Wake of the European Financial Crisis A Review of the Economics and Legal Toolbox - Liu, Yan (IMF Working Papers; Working Paper, 2013)
The private non-financial sector in Europe is facing increased challenges in meeting its debt servicing obligation. In response, governments are revisiting legal tools and-in some cases-institutional arrangements to deal with over-indebtedness. For households, where the problem in some countries is large but no established best practice exists, reforms have generally sought to allow debtors a fresh start while minimizing moral hazard and preserving bank solvency and credit discipline. For the corporate sector, efforts have focused on facilitating debt restruturing (including through out of court mechanisms). Direct government intervention has been rare.